The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1021/acs.est.0c05202
|View full text |Cite
|
Sign up to set email alerts
|

Acute Toxicity of Divalent Mercury to Bacteria Explained by the Formation of Dicysteinate and Tetracysteinate Complexes Bound to Proteins in Escherichia coli and Bacillus subtilis

Abstract: Bacteria are the most abundant organisms on Earth and also the major life form affected by mercury (Hg) poisoning in aquatic and terrestrial food webs. For this reason, identifying the intracellular molecular forms and trafficking pathways of Hg in bacteria at environmentally relevant concentrations is critical to controlling Hg toxicity. We applied high energy-resolution X-ray absorption near edge structure (HR-XANES) spectroscopy to bacteria with intracellular concentrations of Hg as low as 0.7 ng/mg (ppm). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 120 publications
(258 reference statements)
1
12
0
Order By: Relevance
“…Figure illustrates Hg Lα1 HERFD–XAS, using α-HgS, showing the nonresonant X-ray emission Hg Lα1 spectrum (Figure A) and comparing standard Hg L III XAS with the Hg Lα1 HERFD–XAS (Figure B). The dramatic increase in spectroscopic resolution obtained with HERFD−XAS, relative to conventional XAS, and apparent in the figure is in agreement with earlier results from other groups. , Below, we compare Hg Lα1 HERFD–XAS for a wide range of coordination environments and discuss the advantages and limitations of the method as a spectroscopic probe for mercury speciation in complex samples, with a particular focus on environmental and toxicological applications.…”
Section: Introductionsupporting
confidence: 88%
See 1 more Smart Citation
“…Figure illustrates Hg Lα1 HERFD–XAS, using α-HgS, showing the nonresonant X-ray emission Hg Lα1 spectrum (Figure A) and comparing standard Hg L III XAS with the Hg Lα1 HERFD–XAS (Figure B). The dramatic increase in spectroscopic resolution obtained with HERFD−XAS, relative to conventional XAS, and apparent in the figure is in agreement with earlier results from other groups. , Below, we compare Hg Lα1 HERFD–XAS for a wide range of coordination environments and discuss the advantages and limitations of the method as a spectroscopic probe for mercury speciation in complex samples, with a particular focus on environmental and toxicological applications.…”
Section: Introductionsupporting
confidence: 88%
“…The method can eliminate both core-hole and exchange broadening, affording substantial enhancement in spectroscopic resolution. Several studies using Hg Lα1 HERFD–XAS have been previously reported by others. Indeed, this measurement is arguably the most experimentally convenient HERFD–XAS, with an incident energy that is readily accessible on most hard X-ray beamlines and employing the fifth harmonic of Si(111) (the simplest cut) that gives an inherently high reflectivity and narrow Darwin width (∼2.5″) . Moreover, as discussed below, resolution gains with Hg Lα1 HERFD–XAS over conventional Hg L III XAS can be substantial, and for a combination of these reasons, Hg Lα1 HERFD–XAS is often chosen as a first experiment when commissioning HERFD–XAS equipment .…”
Section: Introductionmentioning
confidence: 88%
“…Mercury exerts its toxicity via complexation to cysteinyl (Cys) and selenocysteinyl (Sec) metal binding sites in proteins. , The binding of Hg to Sec residues reduces the Se supply for the biosynthesis of vital selenoproteins. It is usually considered that Hg is detoxified as HgSe and therefore is without toxicological consequences when the molar difference [Se] – [Hg] > 0, or the molar ratio [Hg] mol /[Se] mol < 1, leaving sufficient bioavailable Se for seleoprotein synthesis and activity. , The [Hg] mol /[Se] mol ratio represents the fraction of Se to total Se bound to Hg.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, advancement in the application of high energy-resolution X-ray absorption (HR-XANES) spectroscopy in wildlife identified that MeHg is detoxified to nontoxic mercury selenide (HgSe) through an intermediary Hg-tetraselenolate (Hg­(Sec) 4 ) species. The stepwise transformation of MeHg observed in bird and fish tissues (MeHg → Hg­(Sec) 4 → HgSe), likely initiated by selenoprotein P (SelP), provided the first in vivo mechanistic information for the observation of HgSe in the liver and extrahepatic tissues of marine mammals and seabirds using standard resolution X-ray absorption spectroscopy and electron microscopy. Although these two techniques provide critical structural information on mercury, they provide limited insight into biochemical processes essential for understanding the toxicokinetics of toxic MeHg in organisms (i.e., fate, tissue-specific exchange).…”
Section: Introductionmentioning
confidence: 99%